DESIGN OF DRYER FOR SMALL FARMERS BASED ON THE STUDY OF ERGONOMICS THERMAL ENGINEERING APPLICATION - Bawa Susana, I Gede; Perdana Putra, I Ketut (Universitas Negeri Semarang, 2025)
Ergonomics thermal engineering combines the principles of thermal engineering and ergonomics to design systems and products that optimize energy and resources, improve worker thermal comfort, and reduce thermal stress and fatigue. Small farmers still dry post-harvest food under direct sunlight in open areas. This process produces less than optimal drying thermal temperatures, which impacts long drying times, and dried food is susceptible to dust and animal faeces exposure. In addition, exposure to sunlight on workers causes additional workloads that affect fatigue. This can be overcome by utilizing solar collectors through dryer design based on anthropometric data of workers as users. The dryer was designed through an ergonomics thermal engineering study. Based on anthropometric data and percentile calculations, dimensions were obtained for the dryer design, such as the bottom shelf with a height from the floor of 66.88 cm based on the knuckle, the top shelf height of 123.8 cm from the floor based on standing eye height, and the height of the drying room air chimney from the floor is 177.59 cm based on the height of the upper reach. To avoid new problems with the dryer application, a table was designed as a workaid with a height of 84.31 cm based on the height of the standing elbow. Applying the principles of ergonomics thermal engineering can create systems and products that are more comfortable, safe, and efficient for workers.